Cost‐effectiveness analysis of adding pharmacists to primary care teams to reduce cardiovascular risk in patients with Type 2 diabetes: results from a randomized controlled trial. Issue 7 (2nd February 2015) - Simpson, S. H.; Lier, D. A.; Majumdar, S. R.; Tsuyuki, R. T.; Lewanczuk, R. Z.; Spooner, R.; Johnson, J. A.
Abstract Background Adding pharmacists to primary care teams significantly improved blood pressure control and reduced predicted 10–year cardiovascular risk in patients with Type 2 diabetes. This pre‐specified sub‐study evaluated the economic implications of this cardiovascular risk reduction strategy. Methods One‐year outcomes and healthcare utilization data from the trial were used to determine cost‐effectiveness from the public payer perspective. Costs were expressed in 2014 Canadian dollars and effectiveness was based on annualized risk of cardiovascular events derived from the UKPDS Risk Engine. Results The 123 evaluable trial patients included in this analysis had a mean age of 62 ( ± 11) years, 38% were men, and mean diabetes duration was 6 ( ± 7) years. Pharmacists provided 3.0 ( ± 1.9) hours of additional service to each intervention patient, which cost 226 ( ± 1143) per patient. The overall one‐year per‐patient costs for healthcare utilization were 190 lower in the intervention group compared with usual care [95% confidence interval (CI): ‐1040, 668). Intervention patients had a significant 0.3% greater reduction in the annualized risk of a cardiovascular event (95% CI: 0.08%, 0.6%) compared with usual care. In the cost‐effectiveness analysis, the intervention dominated usual care in 66% of 10 000 bootstrap replications. At a societal willingness‐to‐pay of 4000 per 1% reduction in annual cardiovascular risk, the probability that the intervention was cost‐effective compared with usual care reached 95%. A sensitivity analysis using multiple imputation to replace missing data produced similar results. Conclusions Within a randomized trial, adding pharmacists to primary care teams was a cost‐effective strategy for reducing cardiovascular risk in patients with Type 2 diabetes. In most circumstances, this intervention may also be cost saving.